Clinical and histological evaluation of two dressing materials in the healing of palatal wounds - Shanmugam M; Kumar T.S.S; Arun K; Arun Ramya; Karthik S (Wolters Kluwer Medknow Publications, 2010)
Background : Free gingival grafts have been used extensively for gingival augmentation procedures, but are associated with postoperative morbidity because of the open palatal wound. This study compares the clinical efficiency of two dressing materials, a non-eugenol-based dressing (Coe-Pak™) and a collagen dressing (Colla Cote® ) on palatal wound healing. Materials and Methods : Thirty-two patients in the age group of 25−50 years, who required gingival augmentation, were selected. Free gingival graft was harvested from the palatal mucosa and the wound was then protected using Coe-pak; in control group and Colla Cote; in test group. The subjective parameters pain and burning sensation were recorded on the 2 nd and 7 th day and the objective parameters colour and consistency were recorded on the 7 th and 42 nd day, using a visual analog scale. Thickness of the mucosa was measured using K file at baseline and 42 nd day. Histological examination was done on 42 nd day. Results : The subjective and objective parameters showed significant improvement in the test group when compared to control group. Histologically, there was a greater evidence of collagen formation and turn over in the test group than control group. Conclusions : Collagen-based dressing may thus offer significantly greater advantages over the traditional non-eugenol dressings.